2001
DOI: 10.1042/bj3610143
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a Drosophila homologue of mitogen-activated protein kinase phosphatase-3 which has a high substrate specificity towards extracellular-signal-regulated kinase

Abstract: A partial C-terminal cDNA sequence of a novel Drosophila mitogen-activated protein kinase phosphatase (MKP), designated DMKP-3, was identified from an epitope expressed sequence tag database, and the missing N-terminal cDNA fragment was cloned from a Drosophila cDNA library. DMKP-3 is a protein of 411 amino acids, with a calculated molecular mass of 45.8kDa; the deduced amino acid sequence is most similar to that of mammalian MKP-3. Recombinant DMKP-3 produced in Escherichia coli retained intrinsic tyrosine ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 41 publications
2
38
0
1
Order By: Relevance
“…This hypothesis is supported by data from Chu et al (Chu et al, 1996) who showed that the mammalian Sevenmaker homologue ERK2 D319N is inactivated by DSPs in COS-7 cells at high, but not in NIH3T3 cells at lower expression. The genetic interactions are consistent with a function of DMKP3 between Raf and Rl SEM and strongly support the interpretation that ERK is the main target of DMKP3 (Kim et al, 2002).…”
Section: Dmkp3 Interacts Genetically With Components Of the Ras Pathwaysupporting
confidence: 67%
See 2 more Smart Citations
“…This hypothesis is supported by data from Chu et al (Chu et al, 1996) who showed that the mammalian Sevenmaker homologue ERK2 D319N is inactivated by DSPs in COS-7 cells at high, but not in NIH3T3 cells at lower expression. The genetic interactions are consistent with a function of DMKP3 between Raf and Rl SEM and strongly support the interpretation that ERK is the main target of DMKP3 (Kim et al, 2002).…”
Section: Dmkp3 Interacts Genetically With Components Of the Ras Pathwaysupporting
confidence: 67%
“…In a recent study Kim et al (Kim et al, 2002) have shown that the Drosophila dual specificity phosphatase DMKP3 dephosphorylates ERK, but not JNK or p38 MAP kinases in vitro. Here we provide in vivo evidence in Drosophila that DMKP3 is a phosphatase specific for ERK.…”
Section: Dmkp3 Has a High Specificity Towards Erk In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPK pathway plays a role in the maintenance of tracheal branch integrity, but not through the nuclear effector Pnt Mkp3 has been shown to act as a specific negative regulator of the ERK-type MAPK (Kim et al, 2002;Rintelen et al, 2003). ERK is a central element of the Ras/MAPK pathway whose activity is regulated by phosphorylation (Roux and Blenis, 2004).…”
Section: Overexpression Of Mkp3 Is Responsible For the Branch Integrimentioning
confidence: 99%
“…PTP-ER est ellemême phosphorylée et inactivée par ERK, décrivant ainsi une boucle de rétroaction. Par ailleurs, MKP3, une phosphatase à double spécificité (sérine/thréo-nine et tyrosine) agissant aussi sur ERK, a été mise en évidence par homologie de séquence chez la mouche et le nématode [45,46]. Une étude chez la drosophile a montré que PTP-ER et MKP3 peuvent agir indépen-damment l'une de l'autre, ou de manière concertée selon le contexte cellulaire [47].…”
Section: Apport Des Modèles Génétiquesunclassified